INFLUENCE OF INNOVATION AND BUSINESS ACUMEN IN ENTREPRENEURSHIP SUCCESS IN NIGERIA (NAU Journal of Technology and Vocational Education, 2025)
The study examined innovation and business acumen in entrepreneurship success in Nigeria. Three research questions were analyzed and three hypotheses were tested. A descriptive research design was used. The population of this study comprised all SMEs in Ogun Central Senatorial District of Ogun State Nigeria who have employees spans between 5-55. A total of 50 SMEs in Abeokuta South Local Government Area Ogun State were selected as sample size using purposive random sampling technique. A self-researcher-designed instrument tagged: Innovation, Business Acumen and Entrepreneurship Success Questionnaire (IBAESQ) was used for data collection with (r = .88). Mean and standard deviation were used for answering research questions. PPMC and regression analysis were used for testing hypotheses. The findings of the study revealed that there was a positive relationship between innovation and entrepreneurial success (r = 0.345, p < .05). Business acumen has a positive impact on entrepreneurial performance (β = .381, t = 4.077, p < .05). There was significant composite contribution of independent variables on the dependent variable; R = 0.74, p < .05. The study recommended that business enterprises should engage more on innovation of their production process to improve their product quality and even enhances good enterprises sustainability.
Keywords: Innovation; Business Acumen; Entrepreneurship Success